PELAKSANAAN INOVASI DI BIDANG ADMINISTRASI KEPENDUDUKAN KOTA PAYAKUMBUH - Febri Yanti; Geovani Meiwanda (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Population administration is a series of activities to organize and issue documents through population registration, civil registration, and management of population administration information. The existence of innovation can improve the quality of public services to the community. The innovation